Evaluation of immunohistochemical expression of TWIST in oral epithelial dysplasia and squamous cell carcinoma - Qahtani, Mashael S.; El-Deeb, Amal M.; Metwaly, Hamdy A.M. (International Journal of Health Sciences, 2020)
Introduction: The major transcription factor, which modulates the epithelial-mesenchymal transition in different types of cancers, is known as TWIST oncogene. It binds to the promoter of E-cadherin and suppresses its transcription. The current study aims to assess the expression of TWIST protein in oral squamous cell carcinoma (OSCC), epithelial dysplasia (ED), and normal oral mucosa to verify whether such protein is useful as a marker in oral epithelium malignant transformation. Methods: Thirty-five paraffin-embedded tissue samples of oral lesions with ED and OSCC and five samples of normal oral mucosa were immuostained with anti‑TWIST antibody using the streptavidin peroxidase method. Results: TWIST expression was negative in all cases of normal oral mucosa, whereas all cases of ED and OSCC showed positive immunoreactivity to TWIST varied from weak to strong expression. In ED, there was a significant difference between severe dysplasia and the other two types (P = 0.03). TWIST expression had no significant relationship with the clinical parameters of OSSC clinical stage and grade (degree of differentiation). Only two cases of OSCC with lymph node metastasis showed strong nuclear TWIST expression. Intergroups assessment indicated a significant increase of TWIST expression in OSCC compared to ED (P = 0.000). Conclusion: A significant increase of TWIST expression in OSCC compared to ED may suggest its role in carcinogenesis, it may be a useful marker in malignant transformation of oral epithelium. Therefore, TWIST might be an important target for therapeutic approaches in patients with OSCC, which requires further investigations.